2009
DOI: 10.1111/j.1553-2712.2009.00600.x
|View full text |Cite
|
Sign up to set email alerts
|

Gaps in Procedural Experience and Competency in Medical School Graduates

Abstract: Objectives: The goal of undergraduate medical education is to prepare medical students for residency training. Active learning approaches remain important elements of the curriculum. Active learning of technical procedures in medical schools is particularly important, because residency training time is increasingly at a premium because of changes in the Accreditation Council for Graduate Medical Education duty hour rules. Better preparation in medical school could result in higher levels of confidence in condu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
64
2
2

Year Published

2012
2012
2023
2023

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 97 publications
(79 citation statements)
references
References 11 publications
0
64
2
2
Order By: Relevance
“…Invasive procedural skills are an essential component of resident training. There is ample evidence that there are significant gaps in medical student and resident procedural competence, [100][101][102][103] as well as variability in the correct and safe performance of procedures among residents when performing procedures on patients. 104 There is strong evidence supporting the need for audit and feedback after teaching procedural skills such as central venous catheter insertion to ensure a prolonged and profound behavioral change.…”
Section: Metricsmentioning
confidence: 99%
“…Invasive procedural skills are an essential component of resident training. There is ample evidence that there are significant gaps in medical student and resident procedural competence, [100][101][102][103] as well as variability in the correct and safe performance of procedures among residents when performing procedures on patients. 104 There is strong evidence supporting the need for audit and feedback after teaching procedural skills such as central venous catheter insertion to ensure a prolonged and profound behavioral change.…”
Section: Metricsmentioning
confidence: 99%
“…In a study investigating the proficiencies of newly graduated doctors, the skills noted as being performed more than five times within the first year of junior employment were wound suturing, urinary catheter placement and venipuncture (11). In another study, students who performed a skill more than twice achieved a self-confidence score in that particular skill of 4. out of 5 on average (21).…”
Section: Discussionmentioning
confidence: 99%
“…The pre-training survey showed that PR1 had a low level of confidence with the procedure, even after learning the theory. Promes, et al, 9 reported that less than 29% of …”
Section: Discussionmentioning
confidence: 99%